Influence of shot peened on fatigue bahaviour of suspension arm using strain-life approach - Stanly, Anak Kesulai (2008)
This project describes the influence of shot peened on the fatigue behaviour of suspension arm using strain-life approach. The main objectives of this project are to predict the fatigue life and identify the critical location, to investigate the effect of shot peened treatment and to select the suitable materials for suspension arm. Aluminium alloys are selected as a suspension arm materials. The fatigue life predicted utilizing the finite element based fatigue analysis code. The structural model of the suspension arm was utilizing the solidworks. The finite element model and analysis were performed utilizing the finite element analysis code. In addition, the fatigue life was predicted using the strain-life approach subjected to variable amplitude loading. The three types of variable amplitude are considered in this project. TET10 mesh and maximum principal stress were considered in the linear static stress analysis and the critical location was considered at node (6017). From the fatigue analysis, Smith-Watson-Topper mean stress correction was conservative method when subjected to SAETRN loading, while Coffin-Manson model is applicable when subjected to SAESUS and SAEBRKT loading. From the material optimization, 7075-T6 aluminium alloy is suitable material of the suspension arm compared to 6082-T6. As a conclusion, shot peened treatment was capable to improve the fatigue of the critical location. The significant of this project is to reduce the cost before developing the prototype.